Cooperative spectrum sensing scheme against SSDF attack based on ESD test in radio network - Lichun XIE; Chunqin ZHANG (Dianxin kexue, 2016)
Aiming at the problem that the cooperative spectrum sensing vulnerable to falsify data attacks in cognitive radio network, a cooperative spectrum sensing scheme with against SSDF attack based on test statistic and extreme studentized deviate test was proposed. Firstly, the differential evolution algorithm and weighted gain combining soft decision scheme were combined to form an efficient node decision fusion mechanism. Then, the fault cognitive radio nodes were eliminated by test statistic according to soft statistics data. Finally, the malicious cognitive radio nodes were eliminated by improved ESD test, so as to make a global decision. The simulation results show that the proposed scheme can effectively filter SSDF attack data in cooperative sensing, and it has lower error detection rate.